Factors facilitating nurses to deliver compassionate care: a qualitative study. Issue 1 (3rd February 2017) - Zamanzadeh, Vahid; Valizadeh, Leila; Rahmani, Azad; van der Cingel, Margreet; Ghafourifard, Mansour
Abstract : Background: Compassion is an important ethical foundation of all healthcare professionals especially for nursing. However, there is little understanding of factors which could help and motivate nurses to deliver compassionate care in modern healthcare practices today. Moreover, a cultural context may affect the way compassionate care is delivered by healthcare professionals. Aims and objectives: This study aimed to explore what facilitates compassionate care in daily practice from the unique perspective of Iranian nurses. Research methods: This qualitative exploratory study was conducted in four hospitals. In this study, 16 nurses were selected from various wards. Data were collected by in‐depth, face‐to‐face interviews. For data analysis, a conventional content analysis approach was used. Results: As the most important theme, the theme 'deepening individual's capacity for compassionate care' emerged, which consisted of three categories: the personal system of values and beliefs, patient experience and positive role models of compassion. Conclusions: Addressing and developing nurses' capacity for compassion is possible by providing organisational support and professional education, next to recruiting nurses with a high motivation to relieve patient suffering. These recommendations would help to provide high‐quality compassionate care in healthcare practices. Moreover, nurses could improve their individual capacity for compassion by following their value and belief system and by considering their colleagues as a role model of compassionate practice.